Legal Socialization Related to the Protection of Marine Resources in the Coastal Areas of Ambon Bay - Riry, Welly Angela; Hanafi, Irma Halimah (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: Maluku is a province with its marine characteristics, automatically also has a coastal area. In coastal areas, it also has various functions and important roles for human life, namely hydrologically it plays a role in the preservation of soil and water resources on land, in addition to that it is also related to the preservation of the function of natural ecosystems which from an ecological point of view is a place for the development of various types of fish, shrimp and other marine life, from a biogeophysical point of view as a supporting area for the life of various marine biota and in addition and so on.  The coastal area of Ambon Bay is also an area whose coastal area has been widely used for human activities so that there needs to be an arrangement related to the management and legal protection of its marine resources and this is important to be known by all people living around the coastal area of Ambon Bay.Purposes of The Devotion: The purpose of this is carried out so that the coastal communities of Ambon Bay, especially the people in Poka and Rumahtiga Villages, understand the management arrangements of coastal areas and legal protection related to the natural resources in them.  In addition, this activity is also to get suggestions and input from coastal communities directly which can be study material for the Government. Method of The Devotion: The method of service is by providing legal socialization to the community about legal protection of marine resources in the coastal area of Ambon Bay.Results Main Findings of the Devotion: The findings of this service activity show that there are problems that often occur around the coastal area of Ambon Bay, namely environmental degradation, coastal erosion, uncertainty in natural resource management, vulnerability to natural disasters, socio-economic changes, to marine pollution and overfishing. Discussions with the community also found that there are violations of the law that can occur even though the frequency and type of violations vary such as illegal fishing, overexploitation, marine pollution due to household and market waste, as well as the destruction of mangrove ecosystems and coral reefs and lack of compliance with zoning regulations.